Evaluating Parents' Perspective on Sex Education in Elementary Schools - Melbert Hungo; Leomarich F Casinillo (Jurnal Pendidikan Indonesia, 2023)
Sex education is important to educate young individuals that make them equipped with the right knowledge and attitude concerning healthy sex life. This research article aimed to analyze how parents perceive the integration of sex education in the elementary curriculum of selected public elementary schools in Southern Leyte, Philippines. As for data collection, primary information from parents was considered that include demographic profiles such as age, civil status, educational attainment, religion, and socio-economic status because these factors were believed to affect parents' perceptions. In addition, parents' perceptions of sex education were gathered regarding intellectual, emotional, moral, psychological, and social aspects. The descriptive-correlational research design was employed to elucidate the significant relationship between parents' profile and their perception of the integration of sex education in the elementary curriculum using some standard statistical measures and the Chi-square test. Results showed that parents had strongly unfavorable perceptions of sex education in terms of intellectual, emotional, moral, psychological, and social aspects. Using the Chi-square test, the profile of parents was directly related to their perception of sex education. In conclusion, parents' negative perceptions of sex education at the elementary level are believed to be detrimental to their children because they may lack knowledge of sex education, and in fact, discussing sex education is still considered taboo in the Philippine culture, particularly at the elementary level.